CULTURAL MARGINALIZATION IN N.H SENZAI’S SHOOTING KABUL NOVEL (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
This study aimed at discovering the depiction of cultural marginalization and characters’ resistance in N.H Senzai’s Shooting Kabul novel. The characters of the novel that are Fadi and the member of his family were described experiencing the domination and alienation as the Eastern people. The characters as a minority are marginalized from the society because of the differences in culture. These differences motivate the major society to create a social class, and place the characters in the lower class as a confirmation that they are not equal. The characters judged by their inherent identity, not by their ability. Therefore, the conflict between the characters and the majority becomes a portrayal of cultural marginalization in society. Edward Said’s theory in the concept of Orientalism was used to uncover the issue in Shooting Kabul. The theory discuss about the West as the Occident that dominate the East as the Orient. Furthermore, this study used descriptive qualitative method by describing and analyzing the dialogues and the narrations of the story in the novel. The result of this study described that cultural marginalization was formed by the domination and alienation of the Western people to discriminate the Eastern people. In addition, the study revealed the characters’ resistance as the response of the Western discrimination through silence and fight back.